Analysis of tourist satisfaction models - Sapari, Mohamad Safee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2013)
Ecotourism development has been given serious attention by government of Malaysia. The government has invested a lot of money to develop infrastructures and services to fulfill tourists’ wants. Therefore, the development of ecotourism must consider tourists' preferences at an ecotourism destination. The purpose of this paper is to describe the methods of measurement of the satisfaction level of tourists. Generally, the satisfaction level can be measured by evaluating the gap between tourist expectation and perceived value. There are many of variables may influence the tourists' satisfaction for example people, overall convenience, price, accommodation and food, commodities, attraction, culture and climate and image. Identification of the relationship between the tourists’ expectation and level of satisfaction is necessary for the ecotourism development. A modified framework to measure the satisfaction level is suggested in this paper.